How Does the Social Support Influence Junior College Students’ Occupational Identity in Pre-school Education? - Huang, Jie; Qiao, Tianqi; Song, Zhanmei; Yan, Jingfeng (Frontiers in Psychology, 2022)
Objective This study aimed to investigate the multiple mediating effects of achievement motivation and subjective wellbeing between social support and individual occupational identity. Methods Questionnaire method was used in this study. 565 junior college students majoring in pre-school education were tested by social support scale, achievement motivation scale, subjective wellbeing scale, and occupational identity scale. Results (1) There isn’t significant relationship between perceptions of social support and individual occupational identity. (2) Achievement motivation and subjective wellbeing individually play a mediating role between social support and individual occupational identity. (3) Achievement motivation and subjective wellbeing play a chain mediating effect between elf-efficacy and individual occupational identity. Conclusion Social support can indirectly predict professional identity of pre-school “would-be teachers” through the mediating effect of achievement motivation, subjective wellbeing and the chain mediating effect of achievement motivation and subjective wellbeing.